2013
DOI: 10.1017/s1461145713000631
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol reduces cognitive deficits, amyloid and tau pathology in Alzheimer's transgenic mice

Abstract: The efficacy of antihypertensive agents in Alzheimer's disease (AD) is controversial. It has been tested here whether some antihypertensive drugs might influence AD through mechanisms independent of blood pressure-lowering activity. The effects of treatment with the antihypertensive propranolol on cognition and AD-related markers have been studied in the Tg2576 mouse model of AD. Propranolol, at a lower dose than that used as antihypertensive (5 mg/kg, 6 wk), attenuated cognitive impairments shown by Tg2576 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 54 publications
2
43
1
1
Order By: Relevance
“…Consistent with these findings, the Tg2576 mouse model showed an impairment of contextual fear learning at 4–6 months [7882] when plaques are not yet detectable, but the Aβ42:Aβ40 ratio is modified [80]. This defect worsens with age, [78, 182] and becomes profound at 12–14 months [183, 184]. It should be also noted that the same animals have provided different results in different studies assessing cued learning which was found to be either normal [183, 184] or altered [185].…”
Section: Behavioral Studiesmentioning
confidence: 83%
“…Consistent with these findings, the Tg2576 mouse model showed an impairment of contextual fear learning at 4–6 months [7882] when plaques are not yet detectable, but the Aβ42:Aβ40 ratio is modified [80]. This defect worsens with age, [78, 182] and becomes profound at 12–14 months [183, 184]. It should be also noted that the same animals have provided different results in different studies assessing cued learning which was found to be either normal [183, 184] or altered [185].…”
Section: Behavioral Studiesmentioning
confidence: 83%
“…Tg2576 mice have been reported to have deficits in object recognition [24, 25]. We have shown that OL-1 reverses deficits in object recognition in SAMP8 mice [15].…”
Section: Discussionmentioning
confidence: 99%
“…Tg2576 mice have been reported to have behavioral disinhibition that increases with age compared to the wild type controls [24, 28]. At 9 months of age Tg2576 mice spent significantly greater amount of time in the open arms of an elevated plus maze compared to wild type controls [28] and would freeze less when presented with a loud tone compared to wild type controls [28].…”
Section: Discussionmentioning
confidence: 99%
“…Propranolol, the β-blocker found to ameliorate the stress-induced upregulation of pro-inflammatory myelopoiesis [99], attenuated cognitive deficits, amyloid accumulation, and tau phosphorylation in AD transgenic mice [27]. Genetic inhibition of β2-adrenergic receptors in particular has been shown to reduce tau pathology [138].…”
Section: Part Iv: Isolation and Cognitive Function Dementia And Alzmentioning
confidence: 99%